Pengaruh Sales Growth, Likuiditas, dan Aset Tangibility terhadap Struktur Modal - Chindy Ananda; Asri Winanti Madyoningrum; Syara Purnama Sari; Shafitranata Shafitranata (Penerbit Goodwood, 2024)
Purpose: This study aims to determine the effects of sales growth, liquidity, and asset tangibility on capital structure. Methodology/approach: The research sample included as many as 14 companies in various industrial sectors of the automotive sub-sector for the period 2018-2022. Quantitative research using the associative approach method was used. The data used are secondary data, which are annual financial statements of automotive companies for the period to 2018-2022. The study population comprises various industrial sectors of the automotive subsectors listed on the Indonesia Stock Exchange. The data analysis method used was multiple linear regression using SPSS version 23. Results: The sales growth variable has no significant effect on capital structure, the liquidity variable has a significant effect on capital structure, and the asset tangibility variable has no significant effect on capital structure. Limitations: The sample in the study only focuses on miscellaneous sector companies in various sectors of the automotive industry for the period 2018-2022 listed on the Indonesia Stock Exchange. Contribution: Good sales growth makes investors hesitant to provide capital to the company, and a high liquidity value reflects the ability of the company to meet its short-term obligations. Companies with good liquidity values are considered to have good investor performance. Investors plan and analyze ratios in automotive financial reports to obtain a better understanding and information regarding financial performance. This is performed to achieve a predetermined investment objective.